2011
DOI: 10.1074/jbc.m110.214361
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Cytoplasmic Phosphatase and Tensin Homolog (PTEN)-like Region of Ciona intestinalis Voltage-sensing Phosphatase Provides Insight into Substrate Specificity and Redox Regulation of the Phosphoinositide Phosphatase Activity

Abstract: Ciona intestinalis voltage-sensing phosphatase (Ci-VSP) has a transmembrane voltage sensor domain and a cytoplasmic region sharing similarity to the phosphatase and tensin homolog (PTEN). It dephosphorylates phosphatidylinositol 4,5-bisphosphate and phosphatidylinositol 3,4,5-trisphosphate upon membrane depolarization. The cytoplasmic region is composed of a phosphatase domain and a putative membrane interaction domain, C2. Here we determined the crystal structures of the Ci-VSP cytoplasmic region in three dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
79
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 42 publications
3
79
0
Order By: Relevance
“…Given the striking structural similarity of the intracellular CD of VSPs to PTEN ( 15,27 ), the distinct enzymatic activities may appear surprising. However, the catalytic CX 5 R motif of hVSP (CKGGKGR) differs in a single position from PTEN (CK A GKGR).…”
Section: Enzymatic Properties Of Mammalian Vspsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the striking structural similarity of the intracellular CD of VSPs to PTEN ( 15,27 ), the distinct enzymatic activities may appear surprising. However, the catalytic CX 5 R motif of hVSP (CKGGKGR) differs in a single position from PTEN (CK A GKGR).…”
Section: Enzymatic Properties Of Mammalian Vspsmentioning
confidence: 99%
“…However, the catalytic CX 5 R motif of hVSP (CKGGKGR) differs in a single position from PTEN (CK A GKGR). In Ci-VSP, this amino acid contributes strongly to the 5-phosphatase specifi city ( 26,27 ). Additional sites, including glutamate 411 in the catalytic gating loop of Ci-VSP, are also important for determining substrate selectivity ( 23,25 ).…”
Section: Enzymatic Properties Of Mammalian Vspsmentioning
confidence: 99%
“…Because different substrate reactions are best seen at different voltages, several authors have suggested that changing electric fields can drive VSPs successively through several catalytically active states that favor one set of substrates or reactions over another (20)(21)(22). The active site of VSPs is well conserved among species (12) and shows only a single amino acid difference from the active site of PTEN (1). When this residue in Ci-VSP was mutated to the corresponding amino acid of the PTEN active site, the mutated Ci-VSP still showed both 5-and 3-phosphatase activities toward polyphosphoinositides (14).…”
mentioning
confidence: 99%
“…This enzyme domain is homologous to tumor suppressor phosphatase and tensin homolog (PTEN), a phosphoinositide 3-phosphatase that dephosphorylates both phosphatidylinositol 3,4-bisphosphate [PI(3,4)P 2 ] and phosphatidylinositol 3,4,5-trisphosphate [PI(3,4,5)P 3 ] (1). Three distinctive regions of PTEN, an N-terminal phospholipidbinding motif that anchors the protein at the plasma membrane, a phosphatase domain that has the enzymatic site, and a C-terminal lipid-interacting C2 domain (9,10), are well conserved in sequence and structure in the VSPs (11)(12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation